A study of variable geometry in advanced gas turbines - Roy-Aikins, J. E. A. (Cranfield University, 1988)
The loss of performance of a gas turbine engine at off-design is primarily due to the rapid drop of the major cycle performance parameters with decrease in power and this may be aggravated by poor component performance. More and more stringent requirements are being put on the performance demanded from gas turbines and if future engines are to exhibit performances superior to those of present day: engines, then a means must be found of controlling engine cycle such that the lapse rate of the major cycle parameters with power is reduced. In certain applications, it may be desirable to vary engine cycle with operating conditions in an attempt to re-optimize performance. Variable geometry in key engine components offers the advantage of either improving the internal performance of a component or re-matching engine cycle to alter the flow-temperature-pressure relationships. Either method has the potential to improve engine performance. Future gas turbines, more so those for aeronautical applications, will extensively use variable geometry components and therefore, a tool must exist which is capable of evaluating the off-design performance of such engines right from the conceptual stage. With this in mind, a computer program was developed which can simulate the steady state performance of arbitrary gas turbines with or without variable geometry in the gas path components. The program is a thermodynamic component-matching analysis program which uses component performance maps to evaluate the conditions of the gas at the various engine stations. The program was used to study the performance of a number of cycles incorporating variable geometry and it was concluded that variable geometry can significantly improve the off-design performance of gas turbines.